Carbon and Nitrogen Resorption of Needles As Affected by Compound Fertilizer in a Red Pine Stand. Issue 3 (3rd July 2018) - Baek, Gyeongwon; Yang, A-Ram; Kim, Choonsig
Abstract: This study aimed to examine carbon (C) and nitrogen (N) resorption efficiency between green needles and needle litter in response to compound fertilizer types in a red pine stand. Green needles and needle litter were collected during the growing season (July, September) and during the heavy litterfall season (November) from two compound fertilizer (N3 P4 K1, P4 K1 ) and control treatments. The C concentration of green needles and needle litter was not significantly ( P > 0.05) affected by compound fertilizer, whereas the N concentration in green needles was significantly higher in the N3 P4 K1 than in the P4 K1 and control treatments. C and N resorption efficiency was not significantly affected by compound fertilizer, but N resorption efficiency was significantly affected by sampling month ( P < 0.05). N resorption efficiency was significantly higher in November, followed by September and July. In addition, N resorption efficiency was lower in the current-year needles than in the 1- or 2-year-old needles. These results demonstrate a lack of clear relation between C or N resorption efficiency and N availability in response to the compound fertilizer.